Effects of a Pd/Pt bimetal supported by a γ-Al2O3 surface on methane activation. Issue 8 (14th February 2020) - Hou, Meiling; Zhang, Xin; Fu, Chao; Cen, Wanglai; Chen, Jiaxing
Abstract : Pt is helpful for preventing Pd aggregation and promoting stability. Pd–3Pt/γ-Al2 O3 shows the best catalytic activity for CH4 activation in the presence of water. Abstract : The catalytic removal of methane (CH4 ) in exhaust emissions of natural gas-fueled vehicles is still a major challenge for automotive manufacturers because of the high CH3 –H bond energy and high concentrations of water (H2 O). Density functional theory (DFT) calculations were employed to investigate the adsorption of CH4 and H2 O, as well as the activation of CH4, on the surface of a Pd–Pt bimetal supported by γ-Al2 O3 . These are significant factors for catalytic combustion. Pt addition weakened the bonding of the intermediates and increased the availability of electrons on the surface. Besides this, the γ-Al2 O3 surface and Pt were both beneficial for preventing the aggregation of clusters. CH4 and H2 O adsorption, as well as the detailed mechanism of CH4 activation on the Pd–Pt/γ-Al2 O3 surfaces were simulated. The results showed that a Pt/Pd ratio of three resulted in the best catalytic activity among the different ratios examined in the presence of H2 O.